2007
DOI: 10.1016/j.jeconom.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotics for duration-driven long range dependent processes

Abstract: We consider processes with second order long range dependence resulting from heavy tailed durations. We refer to this phenomenon as duration-driven long range dependence (DDLRD), as opposed to the more widely studied linear long range dependence based on fractional differencing of an i.i.d. process. We consider in detail two specific processes having DDLRD, originally presented in Taqqu and Levy [1986. Using renewal processes to generate long-range dependence and high variability. Dependence in Probability and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The econometric implication of our result is that temporal aggregation of models with heavy tailed regime durations can lead to nonpersistent, although highly leptokurtic, behavior. A similar lack of persistency of long memory seems characteristic also to some other econometric models, in particular, to Parke's (1999) error duration model (see Davidson and Sibbertsen, 2002;Hsieh et al, 2003). See also Davydov (1973) for early probabilistic example of such behavior.…”
Section: Introductionsupporting
confidence: 57%
“…The econometric implication of our result is that temporal aggregation of models with heavy tailed regime durations can lead to nonpersistent, although highly leptokurtic, behavior. A similar lack of persistency of long memory seems characteristic also to some other econometric models, in particular, to Parke's (1999) error duration model (see Davidson and Sibbertsen, 2002;Hsieh et al, 2003). See also Davydov (1973) for early probabilistic example of such behavior.…”
Section: Introductionsupporting
confidence: 57%
“…stable random variables with infinite variance. Such an example may come from durations that obey a positive version of the renewal-reward process discussed in Taqqu and Levy (1986) (see also Hsieh et al (2007)). In such a model, durations would have finite variance but their sums would converge to a process with infinite variance.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that large and small bandwidths correspond to different asymptotic distributions of the kernel estimates. See also Surgailis (2004), Sly and Heyde (2008), Mikosch et al (2002), and Hsieh et al (2007) for similar observations under different settings. In Theorem 5, the lag parameter k n plays a similar role.…”
mentioning
confidence: 86%